miRNA and lncRNA as potential tissue biomarkers in hepatocellular carcinoma - Mallela, Venkata Ramana; Rajtmajerová, Marie; Trailin, Andriy; Liška, Václav; Hemminki, Kari; Ambrozkiewicz, Filip (Non-coding RNA research, 2024)
Hepatocellular carcinoma (HCC) is primary liver cancer, frequently diagnosed at advanced stages with limited therapeutic options. MicroRNAs (miRNAs) regulate target gene expression and through inhibitory competitive binding of miRNA influence cellular processes including carcinogenesis. Extensive evidence proved that certain miRNA's are specifically expressed in neoplastic tissues of HCC patients and are confirmed as important factors that can participate in the regulation of key signalling pathways in cancer cells. As such, miRNAs have a great potential in the clinical diagnosis and treatment of HCC and can improve the limitations of standard diagnosis and treatment. Long non-coding RNAs (lncRNAs) have a critical role in the development and progression of HCC. HCC-related lncRNAs have been demonstrated to exhibit abnormal expression and contribute to transformation process (such as proliferation, apoptosis, accelerated vascular formation, and gain of invasive potential) through their interaction with DNA, RNA, or proteins. LncRNAs can bind mRNAs to release their target mRNA and enable its translation. These lncRNA-miRNA networks regulate cancer cell expression and so its proliferation, apoptosis, invasion, metastasis, angiogenesis, epithelial-mesenchymal transition (EMT), drug resistance, and autophagy. In this narrative review, we focus on miRNA and lncRNA in HCC tumor tissue and their interaction as current tools, and biomarkers and therapeutic targets unravelled in recent years.